A dimensão relacional da arte do presente e o presente da pesquisa sobre o ensino da arte contemporânea em programas de pós-graduação em educação - Trindade, Rogerio Vanderlei de Lima (2017)
The following thesis investigates the relational dimension inscribed in today's art devices and their possible influences on research on the teaching of art today; it is based on the aesthetic theory popularized by philosopher Nicolas Bourriaud – Relational Aesthetics – with his approach to new collective-cognitive-essays, observed in artistic propositions and their forms during the 1990s. This research consisted of an eminently theoretical reflection based on a qualitative bibliographical survey. The central question focused on understanding how relational aesthetics' assumptions are articulated with different approaches to the teaching of contemporary art; this problematic was developed with a view to understanding the modes of appropriation of contemporary art by the educational field – by researches developed in master's and PhD courses in education over the last few years – through analysis, from the point of view of the Relational Aesthetics, of the emerging approaches and discourses on contemporary art today. In order to problematise the discourses that legitimized modern art and other emerging discourses about artworks produced after 1960, the theories proposed by Arthur Danto, Giorgio Agamben, Anne Cauquelin, Jacques Rancière, and others, were used as theoretical support. Other researchers of the intersection between art and education, such as Fernando Hernández, Raimundo Martins and Marilda Oliveira de Oliveira were also included and contributed to the understanding of possible relations between education through art and the most well-accepted artistic propositions nowadays. Thus, after analyzing the scarce production about the topic in this field, the existence of a temporal, conceptual and methodological mismatch between some approaches of the teaching of contemporary art – in addition to the ambiguous presence of the relational dimension in the proposals analysed by the researches –, the existence of a temporal, conceptual and methodological gap between some approaches of the teaching of contemporary art was verified – seen under the light of researches in the field of education and contemporary art production.